Dietary niche separation of rodents and shrews in an African savanna. (14th February 2018) - Namukonde, Ngawo; Simukonda, Chuma; Ganzhorn, Jörg U.
Abstract: While niche separation and relationships with environmental conditions of large mammals of the African savanna have been studied intensively, less conspicuous components have not received similar attention. This is the case of Kafue National Park (KNP), Zambia, where mechanisms supporting coexistence among rodent and shrew species remain unclear, much less the influence of fire on their dietary resource use. Here, we use stable carbon and nitrogen isotopes to assess dietary resource use and partitioning among rodents and shrews found in three vegetation formations of KNP. According to the nitrogen isotope signatures, rodents are one to two trophic levels above primary production, save for Mus triton that is above by two to three. Shrews are two trophic levels above primary production. Among shrews, factors allowing coexistence of similar sized species could not be resolved. Rodent species of the same assemblage either differ in body mass by a factor of two (following Hutchinson's rule) or similar sized species occupy different trophic levels or dietary guilds based on their isotopic nitrogen or carbon signatures. At sites with frequent fires, rodents have broader dietary niches than at sites with low fire frequencies. This could either indicate relaxed competition under high fire frequencies as rodent populations do not reach the carrying capacity of the habitat, or it could reflect reduced competition due to lower species numbers under high versus low fire recurrence regimes. The results indicate competition as an important component structuring rodent communities in Zambian savannas, thus suggesting limited resources.